The effect of antimicrobial photodynamic therapy against virulence genes expression in colistin-resistance Acinetobacter baumannii - Boluki, Ebrahim (Laser Ther, 2019)
BACKGROUND AND AIMS: The emergence of drug-resistant infections is a global problem. Acinetobacter baumannii has attracted much attention over the last few years because of resistance to a wide range of antibiotics. Applying new non-antibiotic methods can save lives of many people around the world. Antimicrobial photodynamic therapy (aPDT) technique can be used as a new method for controlling the infections. In this study we investigated the effect of aPDT on the expression of pathogenic genes in colistin-resistance A. baumannii isolated from a burn patient. MATERIALS AND METHODS: The suspension of colistin-resistance A. baumannii was incubated with 0.01 mg/ml of toluidine blue O (TBO) in the dark; then the light emitting diode device with a wavelength of 630 ± 10 nm and output intensity of 2000–4000 mW /cm(2) was irradiated to the suspension at room temperature. Subsequently, after the aPDT, genes expression of ompA and pilZ was investigated by using real-time polymerase chain reaction technique. RESULT: Among the genes studied, the transcript of the ompA gene after aPDT was increased significantly in comparison with control groups (P < 0.05). Whereas, there was no remarkable different in pilZ gene expression (P > 0.05). CONCLUSIONS: It can be concluded from the results that the ompA as an outer membrane of A. baumannii is degraded after exposing aPDT and it will probably be done the penetration of antibiotics into cells of this bacterium easily.